The Liability of Digital Banks for Data Breaches Occurring in Account Linkage - Pattra, Suvarna Prajna; Kurniawan, Shelly (Dinasti Research, 2025)
The rapid growth of the digital banking sector in Indonesia has introduced innovative services such as Account Linkage, which enables customers to conduct transactions through partner platforms. While this feature enhances banking convenience, it also raises significant concerns regarding data privacy and legal accountability in the event of a data breach. This study aims to analyze the adequacy of existing legal frameworks in regulating data protection within Account Linkage services and to determine whether current Indonesian laws provide sufficient legal certainty. Employing a normative juridical research method, the research reviews statutory regulations, financial authority policies, and relevant contractual agreements. The findings indicate inconsistencies between banking law, financial service regulations, and privacy policies concerning the allocation of liability for data breaches. Moreover, the absence of a specific regulation governing Account Linkage contributes to legal ambiguity, placing consumers at greater risk and complicating the accountability of financial service providers. This study concludes that a more robust and comprehensive legal framework is urgently needed to ensure consumer protection, clarify the responsibilities of digital banks, and support fair and transparent financial innovation.